Assessment of Health-Related Quality of Life of Tuberculosis Patients in Lagos State, Nigeria - Ezinwanyi Madukoma; Olalekan Olayemi (Shahrekord University of Medical Sciences, 2022)
Background and aims: Tuberculosis (TB) is a major public health disease threat in the world, particularly in Nigeria. The burden of TB infection could have a far-reaching effect on the psychological, physical, and social well-being of patients and consequently deterioration in their health-related quality of life (HRQOL). Accordingly, this study examined the HRQOL of TB patients in directly observed therapy (DOT) centers in Lagos State, Nigeria. Methods: The survey design was used for the study, and a total of twelve public DOT Centers were chosen as the study sites. A sample size of 310 was obtained using the Taro Yamane formula. A structured and validated questionnaire was applied to collect data. The World Health Organization Quality of Life Assessment-BREF tool was employed to assess HRQOL. Statistical analysis was conducted using SPSS software, version 23. Results: Based on the results, the overall status of the HRQOL of the studied TB patients was moderate (average weighted mean = 2.48) on a 4-point scale. The finding of the study also highlighted the significant effect of TB on several domains of HRQOL. The psychological domain had the highest HRQOL score (x̅ = 2.60 ± 0.64), while the environmental domain represented the lowest HRQOL score (x̅ = 2.31 ± 0.63). Conclusion: Overall, the HRQOL of TB patients was at a moderate level. The disease had no negative impact on the HRQOL of TB patients across all domains. This finding calls upon strategies to ensure a healthy lifestyle and a conducive living physical environment.